2010
DOI: 10.3109/07853890.2010.514283
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between birth size and coronary heart disease in China

Abstract: Background Clinical epidemiological studies suggested a link between fetal growth conditions and later coronary heart disease (CHD) in adult life. However, no such studies have been conducted in a Chinese population. Objectives We investigated the association between various birth characteristics and CHD occurrence in a Chinese cohort. Design Retrospective cohort study. Setting Peking Union Medical College Hospital, Beijing, China. Participants A total of 2,033 subjects who were born at Peking Union Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
(27 reference statements)
2
19
0
Order By: Relevance
“…In particular focus, the theory has examined the correlations between low birth weight and adult onset of these diseases. Evidence produced has been compelling with a large number of studies across the globe revealing similar results, including the original studies in England [4,5], comprehensive cohort studies in the Nordic countries [6][7][8][9], and more recent studies in non-western countries such as China [10] and also indigenous populations [11,12]. Studies have generally correlated low birth weight, as a result of slowed foetal growth, to be an important indicator in the development of CVD and T2DM.…”
Section: The Early Life Origin Of Health and Disease Theorymentioning
confidence: 86%
See 1 more Smart Citation
“…In particular focus, the theory has examined the correlations between low birth weight and adult onset of these diseases. Evidence produced has been compelling with a large number of studies across the globe revealing similar results, including the original studies in England [4,5], comprehensive cohort studies in the Nordic countries [6][7][8][9], and more recent studies in non-western countries such as China [10] and also indigenous populations [11,12]. Studies have generally correlated low birth weight, as a result of slowed foetal growth, to be an important indicator in the development of CVD and T2DM.…”
Section: The Early Life Origin Of Health and Disease Theorymentioning
confidence: 86%
“…Studies have generally correlated low birth weight, as a result of slowed foetal growth, to be an important indicator in the development of CVD and T2DM. More recent studies have aimed to address limitations in early studies, including the finding that birth weight alone may not be a significant marker in the development of adult onset disease, as well as the uncertainty in low cohort follow-up studies [9][10][11]. For example, the rate of foetal development was identified as a relatively better indicator of disease rather than birth weight alone [11].…”
Section: The Early Life Origin Of Health and Disease Theorymentioning
confidence: 95%
“…[1][2][3][4][5] The burden of abnormal head size also extends into adulthood with documented association with Alzheimer, schizophrenia, and coronary heart disease. [6,7] Both microcephaly and macrocephaly are attributable to chromosomal abnormalities and a variety of environmental factors including congenital infections such as cytomegalovirus (CMV), rubella, and toxoplasmosis. [1,2] The association between sensorineural hearing loss and craniofacial anomalies, syndromes and congenital infections have been extensively documented.…”
Section: Introductionmentioning
confidence: 99%
“…Several cohort studies reported an inverse association between BW and the risk of CHD [5][6][7][8][9][10]. Historical cohort studies in the United States showed that BW and body mass index (BMI) at the age of seven appeared to be independently associated with the risk of CHD in adulthood [7].…”
Section: Introductionmentioning
confidence: 99%